Network disruption detected in GB (United Kingdom) - Voidly (2026)
CRITICAL severity disruption detected in United Kingdom. Confidence: 70%. Data sourced from CensoredPlanet, IODA.
Network Disruption Incident ID: GB-2026-0002
Keywords: internet disruption; GB; disruption; critical